Antibodies against the main immunogenic region of the acetylcholine receptor correlate with disease severity in myasthenia gravis. Issue 9 (4th July 2012) - Masuda, Tomoko; Motomura, Masakatsu; Utsugisawa, Kimiaki; Nagane, Yuriko; Nakata, Ruka; Tokuda, Masahiro; Fukuda, Taku; Yoshimura, Toshiro; Tsujihata, Mitsuhiro; Kawakami, Atsushi
Abstract : Objective: We developed an assay that detects autoantibodies against the main immunogenic region (MIR) located at the extracellular end of the nicotinic acetylcholine receptor (AChR) α subunit, and investigated its clinical relevance in myasthenia gravis (MG). Methods: In this retrospective cohort study, we measured MIR antibody (Ab) titres in sera obtained before treatment and analysed their associations with clinical parameters in 102 MG patients from two neurological centres. MIR Ab titres were determined using a modified competition immunoprecipitation assay in the presence or absence of monoclonal antibody 35. Results: 11 of 23 (47.8%) ocular type and 66 of 72 (91.7%) generalised type MG patients were positive for the presence of MIR Abs, defined as a titre >16.8% (3 SDs above the mean for 70 healthy controls). A significantly higher MIR Ab titre (p<0.001) was shown in generalised type (47.9±19.2%) rather than in ocular type MG patients (16.4±8.4%). Bivariate regression analysis using both titre levels of MIR Ab and routine AChR binding Ab as variables revealed MIR Abs to be an exclusive indicator positively associated with disease severity (Myasthenia Gravis Foundation of America classification, p<0.0001; Quantitative MG score, p=0.008), the presence of bulbar symptoms (p<0.0001) and thymoma (p=0.016), and negatively associated with ocular MG (p<0.0001). Conclusions: MIR Ab titre levels show much better correlations with factors related to disease severity compared with AChR binding Ab titres. The MIR Ab assay may be useful for predicting MG symptom severity, especially for discriminating between ocular and generalised types of MG.